Multicultural Counseling Competence Training: Adding Value With Multicultural Consultation. Issue 3 (2nd July 2016) - Jones, Janine M.; Kawena Begay, Kristin; Nakagawa, Yoko; Cevasco, Molly; Sit, Janelle
ABSTRACT: This study addresses the culturally responsive training process and highlights the integration of multicultural competence building in counseling consultation. Consultation was structured as client-centered case consultation. Before and after the intervention, clinician competence was assessed with the California Brief Multicultural Counseling Competence Scale (CBMCS). Half the clinicians were trained in a culturally responsive model of cognitive behavior therapy (CR-CBT) while the other half were trained in traditional cognitive behavior therapy (CBT). All clinicians participated in weekly client-centered case consultation. The change in CBMCS scores was analyzed and a case study of the sessions comparing two clinicians was completed. The combination of direct training in culturally responsive treatment and case consultation led to significantly greater cultural competence for clinicians in the CR-CBT group. The findings indicate that an intentional effort is required for integrating cultural factors into treatment—one cannot rely solely on the client to acknowledge cultural factors in therapy.